2009
DOI: 10.1007/s00256-009-0674-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of peripheral quantitative computed tomography in identifying disuse osteoporosis in paraplegia

Abstract: Objective: Disuse osteoporosis is a major long-term health consequence of spinal cord injury (SCI) that still needs to be addressed. Its management in SCI should begin with accurate diagnosis, followed by targeted treatments in the most vulnerable subgroups. We present data quantifying disuse osteoporosis in a cross-section of the Scottish paraplegic population to identify subgroups with lowest bone mineral density (BMD). Materials & Methods:Forty-seven people with chronic SCI at levels T2-L2 were scanned usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 19 publications
1
24
0
4
Order By: Relevance
“…6 Treadmill walking has been shown to improve trabecular BMD in the distal tibia but not in the proximal tibia in a case report. 8 The bone mineral content at the distal end is about 50% of that at the proximal ends, and as both proximal and distal metaphyses are loaded primarily in compression it is likely that strains in the distal tibia will be correspondingly larger, perhaps explaining the greater responsiveness of the distal bone to the absence of mechanical stimulus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Treadmill walking has been shown to improve trabecular BMD in the distal tibia but not in the proximal tibia in a case report. 8 The bone mineral content at the distal end is about 50% of that at the proximal ends, and as both proximal and distal metaphyses are loaded primarily in compression it is likely that strains in the distal tibia will be correspondingly larger, perhaps explaining the greater responsiveness of the distal bone to the absence of mechanical stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Although there are large databases of DXA values in the lumbar spine, proximal femur and distal radius, most fractures in SCI patients occur in the distal femur or proximal tibia; these are not sites normally scanned by DXA and therefore there is no large database of controls. pQCT data has been reported for the distal tibia, 6,8 but not together with data on proximal tibia, which is a more common site for fractures in SCI patients. It has been proposed that bone mineral should be measured round the knee, 3 and Rittweger et al measured four sites around the knee, two in the distal femur and two in the proximal tibia.…”
Section: Introductionmentioning
confidence: 98%
“…a severe form of MS can result in a wheelchair bound patient a clinical figure equivalent to paraplegia or a MS patient may have a more appropriate walking gait pattern vs. a patient with incomplete paraplegia but may also be unable to walk at all, is bedridden and vice versa (Dionyssiotis, 2011b;2011c;2011d). In addition to these differences and according to osteoporosis the role of factors which do not change, such as race or gender of patients has not been yet clarified, although there are few studies in women debating that bone mass in women with disabilities is more affected than men (Smeltzer et al, 2005;Coupaud et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…10 Vestergaard et al 11 reported that fractures occur in 2%-6% of people who have suffered a SCI. Cross-sectional densitometry studies 12,13 describe an exponential decrease in bone mineral density (BMD) in the first 3 years after SCI, with BMD reaching a steady-state condition at around 3-7 years post-injury, after which time chronic SCI patients are most susceptible to fracture.…”
Section: Introductionmentioning
confidence: 99%